The cardmaker's workbook : the complete guide to design, color, and construction techniques for beautiful cards - Mason, Jenn (Quarry Books, 2008)
The most complete volume on card making available The Cardmaker's Workbook is the only book on cardmaking that a crafter will ever need, and is formatted in a sturdy volume that can kept on the desk and referred to again and again. The book is divided into chapters focusing on composition, color, theme, construction and inspiration. Instructions are clear but concise, making room for large pictures and multiple variations. It has the look of a designer's notebook with sketches and templates that show different card formats. Unlike other cardmaking books available that are occasion driven or a.